Analisis Pemikiran Ekonomi Islam Imam Abu Hanifah - Nabila Zatadini; Mohammad Ghozali (AL-FALAH : Journal of Islamic Economics, 2018)
Islamic economics has been practiced since the time of the Prophet Muhammad, but at that time until several centuries later there is no classification of specific disciplines for economics, causing some Muslim works lost by the western historians drowned. Therefore it is necessary to study the classical Islamic economic thinking. This paper aims to review Abu Hanifah's economic ideas by comparing it with the opinion of some scholars and match whether Abu Hanifah's thoughts can be used today. The method used is literature research with documentary method to collect data. The results of this study, that Abu Hanifah does not have a special idea in the economy but has a special view in every akqqhatat fiqh such as greetings, charity honey, and hawalah. Some of Abu Hanifah's opinions are different from other priests causing a Muslim today to sort out the khilafiyah.